Remembering Independence - Lentz, Carola, author.
1 online resource (256 pages)
Keywords: Remembering Independence explores the commemoration and remembrance of independence following the great wave of decolonisation after the Second World War. Drawing on case studies from Africa, Asia, and with reference to the Pacific, the authors find that remembering independence was, and still is, highly dynamic. From flag-raising moments to the present day, the transfer of authority from colonial rule to independent nation-states has served as a powerful mnemonic focal point. Remembering independence, in state as well as non-state constructions, connects to changing contemporary purposes and competing politic visions. Independence is a flexible idea, both a moment in time and a project, a carrier of hopes and ideals of social justice and freedom, but also of disappointments and frustrated futures. This richly illustrated volume draws attention to the broad range of media employed in remembering independence, ranging from museums and monuments to textual, oral and ritual formats of commemorative events, such as national days. Combining insights from history and anthropology, this book will be essential reading for all students of the history of empire, decolonisation, nation-building and post-colonial politics of memory.